Abnormal spore morphology and wall ultrastructure in Anemia tomentosa var. anthriscifolia and A. tomentosa var. tomentosa (Anemiaceae) - Ramos Giacosa, Juan Pablo (2014)
The spores of Anemia tomentosa var. anthriscifolia and A. tomentosa var. tomentosa were studied focusing the attention on their abnormalities. The study was based on fresh and herbarium material and the spores were examined with light, scanning and transmission electron microscopy. Normal, abnormal and abortive spores were observed in both taxa. The normal spores were trilete, triangular in polar view, and the ornamentation consisted of parallel ridges separated by narrow and smooth grooves. The spores were observed in monads, dyads, triads and tetrads. The abnormal spores were monolete, trilete, tetralete or alete with great variations in size. In fact, some spores were almost double the size of the normal ones. Some differences were also found in the ornamentation of the spores. Aborted and not completely developed spores were also observed in the specimens. The wall ultrastructure of the taxa was studied for the first time. The exospore was two-layered with numerous cavities inside its structure, and the perispore was also two-layered. The results revealed that the sporoderm ultrastructure of both normal and abnormal spores of the taxa analyzed was very similar.